(untitled) (Mustansiria Dental Journal, 2018)
Bonding of restorative materials to tooth structure has become one of the prime objectives of modern dentistry. The purpose of this in vitro study was to evaluate and compare the shear bond strength of compomer material to dentin washed with three cleanser agent. Thirty freshly extracted adult human maxillary firs, premolars teeth were utilized in this study. Each tooth was sectioned horizontally exposing the dentin surface. According to the type of cleanser agent used to wash the dentin surface; the teeth were divided into three groups often teeth each: Group I chlorhexidine cleanser with compomer; Group II acetic acid with compomer; and Group III distal water with compomer. The measurement for evaluation the shear bond strength of compomer to dentin by using Zwick universal testing machine. The results showed that higher significant different between group I and group III also between group II and group III; however< there is no significant difference between group I and group II. This present in vitro study concludes that the shear bond strength of compomer material to dentin can be enhanced by washing the exposed dentin with cleanser agents chlorhexidine and acetic acid instead of distal water.